Peer Tutoring Implementation for Improved Quran Memorization Quality: Implementasi Tutor Sebaya dalam Peningkatan Kualitas Hafalan Al-Qur’an - Habibah Annabila; Hasrian Rudi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Quran memorization (tahfidz) constitutes a fundamental component of Islamic education, requiring not only retention of verses but also accuracy in tajwid and makhraj. Specific Background: In formal Islamic schools, students often encounter difficulties in memorization due to varied academic abilities and limited instructional time, necessitating collaborative learning strategies such as peer tutoring. Knowledge Gap: Although peer tutoring has been widely discussed in Islamic education contexts, limited studies describe its structured implementation and memorization quality outcomes in emerging tahfidz programs within formal junior secondary schools. Aims: This study aims to describe and analyze the implementation process of peer tutoring in Quran memorization activities at SMP IT Lukmanul Hakim, focusing on planning, implementation, and evaluation stages, as well as memorization quality outcomes. Results: Using a qualitative descriptive field approach with interviews, observation, and documentation, the findings indicate that peer tutoring was implemented through systematic tutor selection based on memorization competence and character, small-group 1:1 rotational guidance, and teacher-supervised evaluation. Approximately 85% of students achieved scores above 80, demonstrating stable memorization performance with improved tajwid application, makhraj accuracy, and fluency, although several students required additional technical guidance. Novelty: The study highlights the integration of technical memorization guidance and tutor character criteria as central variables in a formal Islamic junior high school context. Implications: Peer tutoring represents a structured and contextually adaptable strategy for strengthening Quran memorization quality while maintaining teacher supervision in Islamic educational institutions. Highlights• Systematic small-group rotational guidance produced consistent high memorization scores among most participants.• Technical correction of pronunciation rules was conducted prior to final teacher assessment.• Tutor selection integrated academic competence and moral character as key instructional criteria. KeywordsPeer Tutoring; Quran Memorization Quality; Tahfidz Learning; Tajwid Accuracy; Qualitative Field Research